2017
DOI: 10.1007/s12035-017-0658-4
|View full text |Cite
|
Sign up to set email alerts
|

Fos Protein as a Marker of Neuronal Activity: a Useful Tool in the Study of the Mechanism of Action of Natural Products with Analgesic Activity

Abstract: Pain treatment is still ineffective in many conditions and remains one of the greatest challenges of modern medicine. Historically, due to the incredible variety of pharmacologically promising natural products (NPs) and the chemical complexity of their compounds, scientists have explored their use as a source of treatment for diseases or symptomatology. Fos protein and its precursor, the gene c-Fos, have been the subject of study in relation to the pathophysiology of pain as a possible tool to aid in its under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…Kang et al (2008) demonstrated that oral administration of ursolic acid, a natural pentacyclic triterpenoid carboxylic acid, decreased the number of c-FOS positive neurons in the lumbar spinal cord, causing the inhibition of arthritic nociceptive input to the spinal cord. This finding is in agreement with other studies that reported that terpenes have effective action in inhibiting c-FOS protein expression; and it is also associated with the antinociceptive effect of this molecule (Quintans-Júnior et al, 2016, Santos et al, 2017. Ma and Jiang (Ma and Jiang, 2016), proposed that terpenes are among the most effective compound groups for the treatment of rheumatoid arthritis in traditional Chinese medicine.…”
Section: Modulation Of Signaling Pathways Associated With Inflammatorsupporting
confidence: 92%
See 2 more Smart Citations
“…Kang et al (2008) demonstrated that oral administration of ursolic acid, a natural pentacyclic triterpenoid carboxylic acid, decreased the number of c-FOS positive neurons in the lumbar spinal cord, causing the inhibition of arthritic nociceptive input to the spinal cord. This finding is in agreement with other studies that reported that terpenes have effective action in inhibiting c-FOS protein expression; and it is also associated with the antinociceptive effect of this molecule (Quintans-Júnior et al, 2016, Santos et al, 2017. Ma and Jiang (Ma and Jiang, 2016), proposed that terpenes are among the most effective compound groups for the treatment of rheumatoid arthritis in traditional Chinese medicine.…”
Section: Modulation Of Signaling Pathways Associated With Inflammatorsupporting
confidence: 92%
“…Moreover, the synthesis and secretion of MMP are trigged by increased c-FOS expression, which provokes arthritic joint destruction (Aikawa et al, 2008, Cheung, 2006, Chu et al, 2004, McCarthy et al, 1998. c-FOS protein is routinely used as an indicator for neuronal activation and is expressed in different conditions, including in inflammatory and pain conditions (Santos et al, 2017). Studies have reported that rheumatoid arthritis and osteoarthritis patients present up-regulated c-FOS protein expression in the synovial tissue (Cheung, 2006, McCarthy et al, 1998, Trabandt et al, 1992.…”
Section: Modulation Of Signaling Pathways Associated With Inflammatormentioning
confidence: 99%
See 1 more Smart Citation
“…Fos protein, a marker and research tool for neuronal activation following painful stimuli, is expressed in multiple areas of spinal laminae in response to peripheral inflammation . EA exerts anti‐nociceptive effects at the level of the spinal cord via inhibition of Fos protein expression and interacts with the neural transmission of analgesia via glutamate, cytokines, signal molecules, and norepinephrine .…”
Section: Resultsmentioning
confidence: 99%
“…Neural activation is critical for memory formation with acute stress-induced increases in glucocorticoids necessary for hippocampal neuronal survival, memory acquisition, and consolidation (26). To identify the neural circuitry underlying the differential stress susceptibility between NodDKO(+WAS) and WT(+WAS) mice, we measured expression of the immediate early genes (IEGs) Arc and c-Fos, indicative of neural activation (27, 28). Arc mRNA expression was significantly increased in the hippocampus of WT(+WAS) but not NodDKO(+WAS) mice compared with WT(-WAS) or NodDKO(-WAS) mice respectively (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%